"Etnična demokracija" - Starman, Hannah (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2003)
The author examines the legal and ideological structure of the Israeli state with regard to the citizens it defines as "Israeli Arabs". As a Jewish state and a state for the Jews, Israel is discriminatory by definition; the organisation of the state and its fundamental laws establish this discrimination and facilitate its translation into practice. In the first part, the piece focuses on the conflict that opposes the Zionist ideology to the idea of democracy, which is a subject of ongoing debates among Israeli social scientists, and highlights the main features of the public debate on the nature of the Israeli state and its democracy. Based on one conception of the Israeli citizenship, the author presents, in the second part, the whole complexity of legal and administrative definitions of Israeli citizenship. Thelatter contains discriminatory mechanisms that allow for analytical consideration of the "Arab" minority in Israel as a "trapped" minority, as was suggested by the Israeli antrhopologist, Dan Rabinowitz. In her conclusions, the author argues that such complex and reified systems of recognition of diferrences in cultural repertoirs and provenances of the people as is employed in the Israeli state not only lead to recurrent political cleavages, but also acquire a life of their own that is inert and persistenty not even the best of political wills for egalitarism cannot defeatthem, because it persistenlty behaves as the crucial transfer of power. In this sense, Israel is itself a "trapped" state.
Keywords: Israel; Izrael; Arab; Arabci; narodne manjšine; etnični odnosi; democracy; demokracija; državljanstvo; nacionalizem; nationalism; sionizem; human rights; človekove pravice; pravice manjšin